Association of smoking and electronic cigarette use with wheezing and related respiratory symptoms in adults: cross-sectional results from the Population Assessment of Tobacco and Health (PATH) study, wave 2. Issue 2 (13th February 2019) - Li, Dongmei; Sundar, Isaac K; McIntosh, Scott; Ossip, Deborah J; Goniewicz, Maciej Lukasz; O'Connor, Richard J; Rahman, Irfan
Abstract : Background: Wheezing is a symptom of potential respiratory disease and known to be associated with smoking. Electronic cigarette use ('vaping') has increased exponentially in recent years. This study examined the cross-sectional association of vaping with wheezing and related respiratory symptoms and compare this association with smokers and dual users. Methods: The Population Assessment of Tobacco and Health study wave 2 data collected from October 2014 to October 2015 with 28 171 adults were used. The cross-sectional association of vaping with self-reported wheezing and related respiratory symptoms relative to smokers and dual users of tobacco and electronic cigarettes were studied using multivariable logistic and cumulative logistic regression models with consideration of complex sampling design. Results: Among the 28 171 adult participants, 641 (1.2%) were current vapers who used e-cigarettes exclusively, 8525 (16.6%) were current exclusive smokers, 1106 (2.0%) were dual users and 17 899 (80.2%) were non-users. Compared with non-users, risks of wheezing and related respiratory symptoms were significantly increased in current vapers (adjusted OR (aOR)=1.67, 95% CI: 1.23 to 2.15). Current vapers had significantly lower risk in wheezing and related respiratory symptoms compared with current smokers (aOR=0.68, 95% CI: 0.53 to 0.87). No significant differences were found between dual users and current smokers in risk of wheezing and related respiratory symptoms (aOR=1.06, 95% CI: 0.91 to 1.24). Conclusions: Vaping was associated with increased risk of wheezing and related respiratory symptoms. Current vapers had lower risk in wheezing and related respiratory symptoms than current smokers or dual users but higher than non-users. Both dual use and smoking significantly increased the risk of wheezing and related respiratory symptoms.